2000
DOI: 10.1159/000010270
|View full text |Cite
|
Sign up to set email alerts
|

Serum Angiogenin Levels during Menstrual Cycle and Pregnancy

Abstract: Objective: To evaluate alterations in maternal circulating angiogenin levels with advancing gestation and to assess the effect of labor stress on serum angiogenin levels in neonates delivered vaginally and by cesarean section. Methods: The maternal circulating angiogenin concentrations were compared in 37 normotensive nonpregnant women, in 60 normotensive pregnant women from 7 to 41 weeks of gestation, and in 12 normotensive postpartum women on the 3rd puerperal day. The serum angiogenin concentrations were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Hayashi et al [16] suggested that regulatory mechanisms of angiogenin may exist during pregnancy. Maternal and fetal circulating angiogenin levels did not differ significantly in pregnancies with small-for-gestational age and appropriate-forgestational age infants [17].…”
Section: Introductionmentioning
confidence: 99%
“…Hayashi et al [16] suggested that regulatory mechanisms of angiogenin may exist during pregnancy. Maternal and fetal circulating angiogenin levels did not differ significantly in pregnancies with small-for-gestational age and appropriate-forgestational age infants [17].…”
Section: Introductionmentioning
confidence: 99%
“…Because most tumors form after reproductive age, tumor promotion or suppression itself is not likely to be subject to natural selection, and the selective pressures acting on ANG are most likely related to another, more physiological role for this protein. Several authors have discussed a role for ANG during pregnancy in tissue vascularization of the developing embryo (Hayashi, Yanagihara, and Hata 2000;Koga et al 2000;Malamitsi-Puchner et al 2000). The diversifying selection on ANG may be related to physiologic issues of conflict of interests between mothers and fetuses, as suggested by Haig (1993) in explaining the origin of genetic imprinting.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the concentration of serum ANG increased significantly 2-3 days after the peak luteinizing hormone secretion in women with normal menstrual cycle [22], therefore ANG may play a role in the later stage of menstrual cycle after ovulation. Keiji [23] found that the levels of serum ANG was not significantly different in the normal menstrual cycle of unfertilized female with normal blood pressure. Therefore, whether or not ANG changes in various stages during the menstrual cycle needs further examination in more samples.…”
Section: Ang In Menstrual Cyclementioning
confidence: 96%
“…ANG expression increased significantly in decidua in the endometrium at middle-late secretion, and ANG can stimulate the proliferation of endothelial cells and vascular smooth muscle from decidua, so ANG may involve in embryo implantation, placenta formation and embryonic development [24][25][26][27]. In addition, Hayashi [28] found that during 7 to 15 weeks of pregnancy, the levels of serum ANG kept decreasing, but after 15 weeks, the levels of serum ANG kept rising, so ANG may relate to the whole process of pregnancy including embryo implantation, placenta formation and embryonic development.…”
Section: Ang In Embryo Implantation Placenta Formation and Embryonicmentioning
confidence: 97%